Um estudo sobre a persistência de performance positiva dos fundos IBOVESPA ativos - Bessa, Hudson Antunes (2001)
The objective of this essay is to identify if the positive performance persistence is phenomenon present among active investment funds with relation to the São Paulo stock exchange (IBOVESPA) index. For this purpose, data was used on daily basis for the period from January 1997 to December 2001, of 191 funds which had their performance calculated for each year. In each year studied, at least two groups were defined: one in which were aligned the funds which reflected the best indicators and another in which were present those with the worst performances. The funds that achieved success in remaining in the first group in pairs of consecutive years were called persistent. To be able to measure significance of the results, the instrumental for statistical tests, hypothesis tests, was employed, which tried to identify if the proportions of persistent funds supplied sufficient statistical evidence in order to guarantee the occurrence of the phenomenon in the brazilian market for the researched period.